Testing the simple and complex versions of Gloger's rule in the Variable Antshrike (Thamnophilus caerulescens, Thamnophilidae). (8th May 2020) - Marcondes, Rafael S; Stryjewski, Katherine Faust; Brumfield, Robb T
Abstract : Almost 200 years ago, the German naturalist Constantin Gloger predicted that birds that live in warm and rainy areas tend to be darker than those that in live in cool and dry areas. He also predicted that birds tend to be browner when they live in dry areas. This pattern has come to be known as Gloger's rule. South America has the world's greatest bird diversity, but Gloger's rule has almost never been studied in South American birds. This is an important question to address because it can help us learn about how species evolve respond to their environments. It becomes even more important in our era of human-induced climatic changes. We studied Gloger's rule in the aptly named Variable Antshrike. This small South American bird species varies geographically in color from almost all black to almost all white. We used a technique called reflectance spectrophotometry, which allows us to precisely quantify the colors of feathers. We measured over 200 specimens kept in natural history collections. The majority of those specimens were collected by one of us (Brumfield) in Bolivia in the early 2000s. This is the largest sample size ever used to study Gloger's rule in a tropical bird. As predicted by Gloger, we found that the Variable Antshrike tends to be darker in rainier areas, and it tends to be browner in drier and warmer areas. But contrary to Gloger's ideas, we found that it tends to be darker in cooler, not warmer, areas. We suggest that this might be because being dark in cooler places helps birds maintain warm body temperatures. We also suggest that being brown in dry areas helps the birds camouflage amidst sparse vegetation. Abstract: Gloger's rule is a classic ecogeographical principle that, in its simplest version, predicts animals should be darker in warmer and wetter climates. In a rarely tested more complex version, it also predicts animals should be more rufous in warmer and drier climates. The Variable Antshrike ( Thamnophilus caerulescens ) is a widely distributed South American passerine that presents an impressive amount of plumage color variation and occupies a wide variety of climatic conditions. Moreover, genetic and vocal evidence indicate ongoing hybridization in south-central Bolivia among 3 populations with very distinct plumages. We collected color data from 232 specimens from throughout this species' distribution to test the predictions of Gloger's rule. We found a negative correlation between brightness and precipitation, consistent with the simple version of Gloger's rule. In contrast, we found that birds were darker in cooler climates, contrary to the simple version of Gloger's rule, but consistent with recent findings in other taxa. We found support for both predictions of the complex Gloger's rule and suggest it might be driven by background matching. We conclude by concurring with a recent suggestion that the simple version of Gloger's rule should be reformulated exclusively in terms of humidity. Graphical Abstract: